Character Building through English Language Teaching:: A Case Study at One Junior High School in Palembang - Afifah Marshalina; Dewi Warna; Sartika, Eka (Corolla International Conference, 2023)
The aim of this study was to find out the teaching strategies of English language teachers to build students’ character in English classroom. The participants of this study were two teachers of English at SMP IT Izzuddin Palembang in the academic year of 2020-2021. In this study, the writer applied a qualitative study with case study design, which employ interview instrument for collecting the data. Meanwhile, in order to find out the teaching strategies of English language teachers to build students’ character in English classroom, the data obtained from the interview sessions were analyzed by using thematic analysis. The finding of this study revealed that there were six teaching strategies of English language teachers to build students’ character in English classroom: 1) giving valuable message and model, 2) creating active learning involvement, 3) focusing on students’ outcome, 4) using suitable material resources, 5) applying various activities to shape students’ character, and 6) evaluating students’ character. In short, teachers had applied character building in English classroom. Through the teaching strategies implemented by the teachers regularly, it would affect students’ competence in English skill and improve their character.